BIOLOGICAL ACTIVITY OF ESSENTIAL OIL OF PITANGA (Eugenia uniflora L.) LEAVES - Sviech, Fernanda; Pianoski, Karlos Eduardo; Kruger, Roberta Letícia; Kotovicz, Valesca; Molardi Bainy, Eduarda M. Bainy; Sakata, Guilherme Shigueru Barbosa; Mesomo Bombardelli, Michele Cristiane (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2019)
Natural extracts present antioxidant activity and can replace synthetic antioxidants. This study aimed to extract essential oil from Pitanga (Eugenia uniflora L.) leaves and evaluate its chemical composition, as well as antioxidant and antibacterial activities. The essential oil was obtained by hydrodistillation for 3 hours with a yield of 1.34 ± 0.18 %. The total antioxidant activity was evaluated by the DPPH and phosphomolybdenum methods. The oil presented an IC50 value of 100.96 µL mL‑1 and 1503.44 ± 29.48 mg α‑tocopherol mL-1 of oil. The major compounds identified by the GC-MS were germacrone (13.57%), spathulenol (7.49%), curzerene (5.31%) and α-cadinol (4.70%). The oil was also evaluated for its antimicrobial activity and was effective against Staphylococcus aureus. These results show that essential oil of pitanga leaves have good antioxidant and antimicrobial activity, being an alternative source of bioactive compounds.